Characteristics of SPLDV and POAC Management in The Perspective of Sales Optimization - Herinanto, Dwi; Hakim, Lukmanul; Gumanti, Miswan; Helmita, Helmita; Batara, Ivan (Proceeding International Conference on Information Technology and Business, 2023)
Implementation of POAC management carried out by CV’s manager includes the planning, namely creating an appropriate model design; the organizing, namely carrying out analysis and solutions; the actuating, namely formulating ways to gain profit; and the controlling, namely providing recommendations. This research is multidisciplinary research because it involves two academic disciplines (mathematics and management) to solve a particular problem together.Keywords: POAC, management, linier programming